On the Optimization of Cholesterol Screening - Milsum, J. H. (Methods of Information in Medicine, 1991)
Total serum cholesterol is a major risk factor for Coronary Heart Disease (CHD). Some guidelines have been published regarding treatment levels. However, before implementing cholesterol screening, the costs and benefits should be analyzed as a function of cholesterol level. Analysis is readily implemented on microcomputer spreadsheets using decision tree analysis. Because it is very difficult to establish some of the costs satisfactorily, the facility of spreadsheets in performing sensitivity analysis is crucial. Here, plausible numerical values are used as “default” conditions for estimating in a preliminary way the costs and benefits of a putative screening-intervention program. The cost-benefit condition remains very close to optimal over the range 200-240 mg/dl for cholesterol marker level. The optimal condition may shift considerably when the default parameter values are altered. With the default values, the maximal net benefit is around 5% of the estimated current costs of CHD deaths without screening.
Keywords: Cholesterol; Screening; Decision Tree; Optimization; Spreadsheets